Beneficial Effects of Whole Body Vibration on Brain Functions in Mice and Humans - Ate S. Boerema; Marelle Heesterbeek; Selma A. Boersma; Regien Schoemaker; Erik F. J. de Vries; Marieke J. G. van Heuvelen; Eddy A. Van der Zee (SAGE Publishing, 2018)
The biological consequences of mechanical whole body vibration (WBV) on the brain are not well documented. The aim of the current study was to further investigate the effects of a 5-week WBV intervention on brain functions. Mice (C57Bl/6J males, age 15 weeks) were exposed to 30 Hz WBV sessions (10 minutes per day, 5 days per week, for a period of 5 weeks; n = 10). Controls received the same intervention without the actual vibration (n = 10). Humans (both genders, age ranging from 44-99 years) were also exposed to daily sessions of 30 Hz WBV (4 minutes per day, 4 days per week, for a period of 5 weeks; n = 18). Controls received the same protocol using a 1 Hz protocol (n = 16). Positron emission tomography imaging was performed in the mice, and revealed that glucose uptake was not changed as a consequence of the 5-week WBV intervention. Whole body vibration did, however, improve motor performance and reduced arousal-induced home cage activity. Cognitive tests in humans revealed a selective improvement in the Stroop Color-Word test. Taken together, it is concluded that WBV is a safe intervention to improve brain functioning, although the subtle effects suggest that the protocol is as yet suboptimal.